2020
DOI: 10.1080/07481187.2020.1784311
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of the COVID-19 Perceived Risk Scale: A preliminary study

Abstract: This study adapted an 8-item COVID-19 Perceived Risk Scale (CPRS) to assess COVID-19 related personal risk. The sample comprised 3,109 Turkish adults (49.98% males; Mean age ¼ 38.64 ± 10.40). Exploratory and confirmatory factor analyses confirmed a two-factor structure (cognitive and emotional dimensions), with satisfactory reliability. The subscales were correlated with severity and self-efficacy related to COVID-19 and mental health. Women reported higher levels of emotional risk, overall risk, and severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
189
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(212 citation statements)
references
References 42 publications
14
189
0
9
Order By: Relevance
“…Only few studies examined the relationship between severity, self-efficacy, and mental health in the context of COVID-19. Higher severity, and lower self-efficacy were found to be related with poor mental health (Yıldırım & G€ uler, 2020). Another study found a negative relationship between general self-efficacy and psychological distress during COVID-19 pandemic (Shacham et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Only few studies examined the relationship between severity, self-efficacy, and mental health in the context of COVID-19. Higher severity, and lower self-efficacy were found to be related with poor mental health (Yıldırım & G€ uler, 2020). Another study found a negative relationship between general self-efficacy and psychological distress during COVID-19 pandemic (Shacham et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…The CPRS measures the COVID-19 related to personal risk ( Yıldırım & Güler, 2020 ). The scale includes 8 items and two dimensions (cognitive and emotional).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores reflect greater risk related to COVID-19. Yıldırım and Güler (2020) reported that the CPRS has a two-factor structure (shown through exploratory and confirmatory factor analyses), good convergent validity with COVID-19 severity, self-efficacy, and mental health and high internal consistency reliability.…”
Section: Methodsmentioning
confidence: 99%
“… Yıldırim and Güler (2020) developed the 8-item COVID-19 Perceived Risk Scale (CPRS) to assess perceived risk of infection. They amended the 8-item SARS Risk Perception Scale ( Brug et al, 2004 ) and, like it, theirs included a cognitive dimension (focusing on the perceived likelihood of COVID-19 infection) and an emotional dimension (focusing on worry about significant others contracting the virus).…”
Section: Introductionmentioning
confidence: 99%